THE EFFECT OF EMOTIONAL INTELLIGENCE LEVELS OF TOURISM STUDENTS ON THEIR CRITICAL THINKING DISPOSITION - Sönmez, Neslihan Kan (Fırat University, 2023)
When considering the necessities of this age, critical thinking is a primary skill that tourism students should be qualified in. Investigation on the critical thinking disposition of tourism students and emotional intelligence, which is an effective factor on it, can guide tourism academics on how to provide students with effective critical thinking. In this regard, this study aimed to determine the effect of the emotional intelligence levels of the undergraduate tourism education students on their critical thinking disposition. A survey was utilized as data collection tool, and it was administrated on a total of 471 students from undergraduate tourism schools of 5 different universities, including 3 faculties and 2 colleges. The data were analyzed by frequency, percentage distribution, arithmetic mean, standard deviation, t test, analysis of variance and Pearson correlation analysis. The research concluded that students' emotional intelligence levels and critical thinking dispositions were quite above the medium level. In addition, a positive and strong correlation of r=0.671 was specified between emotional intelligence levels and critical thinking dispositions of the students. It was also found out that students' emotional intelligence levels and critical thinking dispositions showed significant differences according to the variables of gender, academic success and monthly expense.

Eleştirel düşünme, eğitimin en önemli ilkelerinden biri olup, her ülkenin büyüme ve refaha ulaşmak için eleştirel düşünmeye ihtiyacı bulunmaktadır. Duygusal zekâ, eleştirel düşünmenin önemli bir yordayıcısıdır. Bir kişinin duygusal zekâsı geliştikçe, eleştirel düşünme eğilimi de artmaktadır. Bu doğrultuda araştırmada, lisans düzeyinde turizm eğitimi alan öğrencilerin duygusal zekâ düzeylerinin eleştirel düşünme eğilimi üzerindeki etkisinin belirlenmesi amaçlanmıştır. Araştırmada veri toplama tekniği olarak anket kullanılmış ve 3 fakülte, 2 yüksekokul olmak üzere 5 farklı üniversitenin lisans düzeyindeki turizm okullarından toplam 471 öğrenci üzerinde uygulama gerçekleştirilmiştir. Verilerin analizinde frekans, yüzde dağılımı, aritmetik ortalama, standart sapma, t testi, varyans analizi ve Pearson korelasyon analizi kullanılmıştır. Araştırma sonucunda, öğrencilerin duygusal zekâ düzeyleri ile eleştirel düşünme eğilimlerinin orta düzeyin oldukça üzerinde olduğu tespit edilmiştir. Bununla birlikte öğrencilerin duygusal zekâ düzeyleri ile eleştirel düşünme eğilimleri arasında r=0,671’lik pozitif ve kuvvetli bir korelasyon bulunmuştur. Ayrıca, öğrencilerin duygusal zekâ düzeyleri ile eleştirel düşünme eğilimlerinin cinsiyet, akademik başarı ve aylık harcama değişkenlerine göre anlamlı farklılıklar gösterdiği saptanmıştır.
Turizm Öğrencilerinin Duygusal Zekâ Düzeylerinin Eleştirel Düşünme Eğilimi Üzerindeki Etkisi